2017
DOI: 10.3174/ajnr.a5239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultra-Low-Dose and Iterative Reconstructions on the Visualization of Orbital Soft Tissues on Maxillofacial CT

Abstract: Compared with a reference dose protocol with FBP, model-based iterative reconstruction may show similar diagnostic visibility of orbital soft tissues at a CT dose index volume of 2.64 mGy. Low-dose technology and iterative reconstruction technology may redefine current reference dose levels in maxillofacial CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…The decrease in SNR and CNR seems to maintain with the standalone use of the IR, raising the strength from one to five, after radiation dose reduction. A prior study also found that both adaptive statistical IR and model-based IR had a significantly better CNR than FBP for the optic nerve and inferior rectus muscle 18 . Other studies provided a potential for radiation dose reduction using an IR algorithm for soft tissue datasets of cranial CTs 19,20 .…”
Section: Discussionmentioning
confidence: 82%
“…The decrease in SNR and CNR seems to maintain with the standalone use of the IR, raising the strength from one to five, after radiation dose reduction. A prior study also found that both adaptive statistical IR and model-based IR had a significantly better CNR than FBP for the optic nerve and inferior rectus muscle 18 . Other studies provided a potential for radiation dose reduction using an IR algorithm for soft tissue datasets of cranial CTs 19,20 .…”
Section: Discussionmentioning
confidence: 82%
“…Iterative Bildrekonstruktionen mit komplexen mathematischen Rechenmodellen verbessern die Bildqualität von dosisreduzierten Untersuchungen und zeigen in Abhängigkeit vom verwendeten Algorithmus und der klinischen Fragestellung eine mögliche Dosiseinsparung von bis zu 80 % [22]. Für die Zahn-und Kieferheilkunde konnten bereits folgende indikationsspezifische ALADA-CT-Dosen (CTDIvol) ermittelt werden: Trauma Mittelgesicht 2,6 mGy [23,24]; Implantologie mit Detektion und Messgenauigkeit des Mandibularkanals 1,74 mGy [25] bzw. lineare Messgenauigkeit des Implantatbetts 0,29 mGy [26,27]; Herstellung von CAD-Modellen 0,99 mGy [28]; und Computer-assistierte Chirurgie 0,76 mGy [29].…”
Section: Rechtfertigende Indikationunclassified
“…The effective dose of a CBCT is known to be lower, ranging from 0.08 to 0.21 mSv on average, depending on the field of view that is used [34]. However, the effective dose of both a CT and CBCT can vary significantly based on a multitude of factors such as the system type, scan range, size of the patient and scan protocol parameters [25,34,36,39]. Hence, the interest in investigating whether physical examinations can be used to diagnose a fracture so as to reduce unnecessary imaging, health care costs and exposure to ionizing radiation [40,41].…”
Section: Introductionmentioning
confidence: 99%